Madrasah Financial Management Based on Edm and E-Rkam at MTS Miftahul Huda, Bandung City - Taorena Sandra; Muhamad Makin Shalahuddin; Badrudin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study examines technology-based financial management at MTs Miftahul Huda Kota Bandung using the Evaluasi Diri Madrasah (EDM) and e-RKAM for managing the madrasah’s finances. The research employs a qualitative descriptive method, with data collected through observation, interviews, and documentation. The findings reveal that EDM is utilized to assess priority needs, which are then incorporated into the Rencana Kerja dan Anggaran Madrasah (RKAM), with primary funding sources derived from BOS (school operational funds) and parental contributions (KBM fees). The implementation of technologies such as EDM, e-RKAM, and the Financial Information System (SIKOS) has enhanced efficiency and accountability in financial management. Challenges include system socialization among stakeholders and limited external funding sources. This study recommends increasing stakeholder training and diversifying funding sources to support the sustainability of madrasah financial management.